Public Relations And Leadership In Islamic Education Institutions - M. Kurma (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2022)
The purpose of this study was to describe public relations and leadership in Islamic educational institutions. The research method in this study uses a qualitative approach and the type of research is library research. The results of his research show that public relations is an intermediary between the leaders of the organization as well as on maintaining publicnya community, internal and external to the public relations profession is generally believed and facilitation, motivation, and become agents of change for educational institutions. Organize or collectively, in desperate need of a leader who has the ability to play a role in improving human resource capabilities. Therefore, the leaders of the organization wherever possible serves as a bellwether for human resources and where possible be an agent of change, a spokesman and trainer. Absence of a leader role in the success of the organization is reflected in the leadership style that is applied to influence his followers. The leadership style in question is the appropriate leadership style to the needs of his followers with the intention of being able to make his act together ffor achieve the goals of an organization.